Komodifikasi agama dalam konten influencer religi di media sosial - almubarok, ahmad faiz romadhon (Maliki Interdisciplinary Journal, 2026)
This research aims to analyze the phenomenon of religious influencers on social media and the accompanying process of religious commodification in modern society. Employing a qualitative approach with a library research method, this study examines the phenomenon through the lens of the Frankfurt School's critical theory, specifically the concept of the culture industry. The findings indicate that advancements in information technology have transformed da'wah methods to be more practical, creative, and interactive, making them highly appealing to Generation Z. However, the presence of religious influencers also triggers a commodification process where religious symbols and teachings shift from "use value" to "exchange value" for the sake of popularity, follower counts, and economic gain. The logic of social media algorithms often reduces the depth of theological meaning in favor of sensational and viral content. Although digital da'wah effectively increases religiosity, the risk of superficial understanding persists due to the lack of face-to-face interaction. This study concludes that an integration between inclusive digital da'wah and profound traditional guidance is necessary to maintain the purity of spiritual messages. Influencers are expected to prioritize da'wah ethics, while the public must be more discerning in filtering religious content in cyberspace.